TECHNOLOGIES FOR THE CONSERVATION OF ART AND CULTURAL HERITAGE. ARTIFICIAL INTELLIGENCE ALGORITHMS IN APPLICATIONS (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
Today, the integration of Artificial Intelligence algorithms into emerging technologies has gained popularity in various fields of work. Such integration has revolutionised the way in which challenges associated with the preservation of works of art, antiquities and other cultural heritage are addressed. This research presents a systematic review of the application of machine learning algorithms and computer vision in the identification and analysis of materials, damage and alterations in works of art. These tools allow for a more accurate and detailed assessment, facilitating early detection of potential threats to the integrity of the artworks, and not only preserving the original appearance, but also offering new insights into the history and context of the works. Subsequently, some generative art algorithms were identified, as well as predictive and monitoring algorithms to assess the impact of the environment on the exhibited artworks, allowing precise adjustments in storage and exhibition conditions to prevent long-term damage. Finally, the transformative potential of these algorithms (StyleGAN, BigGAN, CNN, fuzzy systems, evolutionary algorithms, swarm intelligence, Autoencoders, SRGAN, Neural Style Transfer, Histogram Equalization, Non-Local Filters, Wavelet Transform, Kalman Filters, Data Augmentation, U- Net, ResNet, VGG16) is highlighted and ethical and cultural considerations associated with their implementation are raised. The combination of art conservation technologies and artificial intelligence algorithms offers a promising outlook for the preservation and continued appreciation of our valuable cultural heritage.
Keywords: Applications; Algorithms; Artificial Intelligence; Art; Cultural Heritage